Effect of Loads on Tribological Performance of Rubber Seals at Floating Wind Power in Deep Sea - Guibin Tan; Cheng Zhou; Jiantao Liang; Guangjing Huang; Zhixing Wang; Xing Huang (Lubricants)
The main shaft seal of offshore wind power equipment is one of the key components of wind power systems. However, wear issues between the seals and the main shaft caused by the intrusion of particulate matter in the environment have become a key factor affecting the service life of the equipment. To improve the surface performance of the main shaft, this study used laser cladding technology to prepare an Fe55 coating on the surface of QT-500 components. Through the wear experiments on HNBR seal pairs with the main shaft under different load conditions, this study thoroughly investigated the impact of the coating on frictional coefficients, wear mechanisms, and the wear morphology of metal surfaces. The experimental results show that the average hardness of the Fe55 coating is 533 HV, which is about 2.3 times the hardness of the substrate, and as the loading force increases, the wear form of the QT-500 metal changes from being dominated by pits to being dominated by furrows. In contrast, the wear form of the Fe55 coating is more inclined to furrows, and no pit formation is observed, indicating that the coating has improved the wear resistance of the surface. The frictional coefficient of the HNBR pair with the metal decreases with increasing load, and the frictional coefficient of the coating is lower than that of the substrate. As the loading increases, the wear morphology of the rubber surface transitions from furrows to pits, and the wear mechanism becomes abrasive wear.